2009
DOI: 10.1186/1471-2458-9-300
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported pediatricians' management of the well-appearing young child with fever without a source: first survey in an European country in the anti-pneumococcal vaccine era

Abstract: Background: Recent studies suggest a substantially reduced risk of invasive bacterial infection in children vaccinated with heptavalent pneumococcal conjugate vaccine (PCV). To investigate whether the introduction of PCV might affect clinical decision making, we conducted a crosssectional survey aimed at Italian Pediatric physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Not only Lab-score recommendations, but also classical guidelines concerning FWS management are poorly observed. Indeed, now that the incidence of SBI has dropped following widespread pneumococcal vaccination [28] , [29] , a more conservative approach of well appearing infants or young children with FWS is frequently adopted [2] , [30] [32] . A recent study observed a decrease in ordering a complete blood count between 2004 and 2009 [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Not only Lab-score recommendations, but also classical guidelines concerning FWS management are poorly observed. Indeed, now that the incidence of SBI has dropped following widespread pneumococcal vaccination [28] , [29] , a more conservative approach of well appearing infants or young children with FWS is frequently adopted [2] , [30] [32] . A recent study observed a decrease in ordering a complete blood count between 2004 and 2009 [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Gabriel et al found that pediatricians and emergency department physicians would order fewer tests and would prescribe less antibiotics to febrile children who have been vaccinated previously with pneumoccoal conjugate vaccine [ 18 ]. Chiappini et al found that the management of well-appearing febrile infants varies across pediatricians in Italy after the introduction of the pneumococcal conjugate vaccine [ 13 ]. Although most pediatricians in our study reported some reliance on the fever management guidelines set forth by the American Academy of Pediatrics (AAP), it is apparent that the general attitude of pediatricians towards fever management has been changing since the introduction of the pneumococcal conjugate vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Such work evaluating physicians' perception and approach to the management of fever in infants is now quite dated, however [ 10 - 12 ]. Beliefs among some pediatricians have changed after the introduction of pneumococcal conjugate vaccines [ 13 ]. Because of the high efficacy of the pneumococcal vaccine against invasive infections of Streptococcus pneumoniae , some pediatricians have practiced less intensive diagnostic procedures for the standard work-up of fever [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The arrival of Hib and pneumococcal conjugate vaccines in Japan will influence the methods used for ruling out the indication for antibiotics. A previous study showed that physicians prescribe antibiotics less frequently in vaccinated patients than in patients who have not been vaccinated 89) . The vaccines may contribute not only to decrease the incidence of invasive diseases caused by S. pneumoniae and H. influenzae but also to decrease antibiotic prescription for pediatric patients.…”
Section: The Introduction Of Vaccines Against S Pneumoniae and H Inmentioning
confidence: 98%